THE ROLE OF MEDIA TEXT IN THE PROCESS OF INCREASING CONSCIOUS SUPPORT FOR IMPORTANT ISSUES - Gabinashvili, Irma (International Journal of Innovative Technologies in Social Science, 2023)
Among the fields that use rhetoric as an art of verbal persuasion for effective manipulation and increasing credibility in society like political science, psychology, sociology, linguistics, communicative linguistics, literary studies, etc., we should highlight a segment that is interesting to us - communication and one of its "weapons" - media text, for which the theory of rhetorical argumentation is the main pillar to influence the audience. The transition to the media-based global cultural environment and the claim to the media - as if it degrades high, elite culture, lost its relevance and was modified in a new direction - by forming the role of a counter-producer in cultural processes. Development of media is a continuous and irreversible process, where the forms of communication change periodically, the language of the media, which is one of the important areas of action and creativity, remains unchanged. That is why it is important to study Architecture and context of media text in the process of producing effective communication and raising awareness of public support.